2005
DOI: 10.1124/jpet.105.085928
|View full text |Cite
|
Sign up to set email alerts
|

Tertiapin-Q Blocks Recombinant and Native Large Conductance K+ Channels in a Use-Dependent Manner

Abstract: Tertiapin, a short peptide from honey bee venom, has been reported to specifically block the inwardly rectifying K ϩ (Kir) channels, including G protein-coupled inwardly rectifying potassium channel (GIRK) 1ϩGIRK4 heteromultimers and ROMK1 homomultimers. In the present study, the effects of a stable and functionally similar derivative of tertiapin, tertiapin-Q, were examined on recombinant human voltage-dependent Ca 2ϩ -activated large conductance K ϩ channel (BK or MaxiK; ␣-subunit or hSlo1 homomultimers) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 37 publications
2
65
0
Order By: Relevance
“…Moreover, when heterologously expressed in H9C2 cells (a rat embryonic heart-derived cell line), a ROMK2 construct with a COOH-terminal tag was found to localize to intracellular compartments positive for mitochondrial markers (240). The same study also demonstrated that diazoxide-induced changes in mitochondrial matrix volume and thallium flux into mitochondria are abrogated by tertiapin Q, a peptide isolated from bee toxin that blocks certain types of inwardly rectifying K ϩ channels, including Kir1.x (ROMKx), G protein-activated K ϩ channels (Kir3.x or GIRK1/4) (404,441), and the Ca 2ϩ -activated large-conductance K ϩ channel (BK or MaxiK) (423). Although this result is intriguing, the possibility that ROMK subunits may constitute the pore-forming components of mitochondrial K ATP channels remains to be independently confirmed by other laboratories and with genetic approaches.…”
Section: Kir11 Subunitsmentioning
confidence: 89%
“…Moreover, when heterologously expressed in H9C2 cells (a rat embryonic heart-derived cell line), a ROMK2 construct with a COOH-terminal tag was found to localize to intracellular compartments positive for mitochondrial markers (240). The same study also demonstrated that diazoxide-induced changes in mitochondrial matrix volume and thallium flux into mitochondria are abrogated by tertiapin Q, a peptide isolated from bee toxin that blocks certain types of inwardly rectifying K ϩ channels, including Kir1.x (ROMKx), G protein-activated K ϩ channels (Kir3.x or GIRK1/4) (404,441), and the Ca 2ϩ -activated large-conductance K ϩ channel (BK or MaxiK) (423). Although this result is intriguing, the possibility that ROMK subunits may constitute the pore-forming components of mitochondrial K ATP channels remains to be independently confirmed by other laboratories and with genetic approaches.…”
Section: Kir11 Subunitsmentioning
confidence: 89%
“…First, unlike U73122, tertiapin is also an equally potent blocker of Kir1 channels (Jin and Lu, 1998). Second, in contrast to the inhibitory effect of U73122, block of BK channels by tertiapin is slow and use-dependent requiring strong and prolonged depolarization to develop (Kanjhan et al, 2005). Thus, tertiapin (300 nM) did not produce any suppression of BK channels when we used the same recording conditions that reliably revealed the blocking action of U73122 (physiological K ϩ gradient, V h , 0 mV; data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…Tertiapin was introduced as a specific and potent blocker of Kir3 channels at nanomolar affinity, whereas Kir2 channels remained insensitive (Jin and Lu, 1998). More recently, tertiapin was also found to inhibit BK channels (Kanjhan et al, 2005). Its mechanism of action is not fully resolved, but tertiapin is thought to occlude the channel by plugging its ␣ helix into the external vestibule of the ion conduction pore (Jin et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified peptide toxins that modulate BK channels from venoms of various animals including scorpion (28 -30), cone snail (31), snake (32), bee (33), and spider (34). Among these toxins, charybdotoxin (ChTx) and iberiotoxin (IbTx) have been intensively studied for molecular pharmacology and used as an effective tool to identify BK channels in various tissues that contributed greatly in the understanding (Fig.…”
Section: Discussionmentioning
confidence: 99%